**Given : **A right ΔABC right angled at B

**To prove : **AC^{2} = AB^{2} + BC^{2}

**Construction :** Draw AD ⊥ AC

**Proof :** ΔABD and ΔABC

∠ADB = ∠ABC = 90°

∠BAD = ∠BAC (common)

∴ ΔADB ∼ ΔABC (by AA similarly criterion)

⇒ AD × AC = AB^{2} ...... (1)

Now In ΔBDC and ΔABC

∠BDC = ∠ABC = 90°

∠BCD = ∠BCA (common)

∴ ΔBDC ∼ ΔABC (by AA similarly criterion)

⇒ CD × AC = BC^{2} ........ (2)

Adding (1) and (2) we get

AB^{2} + BC^{2} = AD × AC + CD × AC

= AC (AD + CD)

= AC × AC = AC^{2}

∴ AC^{2} = AB^{2} + BC^{2}

89% users found this answer helpful.